2013
DOI: 10.1155/2013/671545
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Trace Elements on the Lipid Productivity and Fatty Acid Composition ofNannochloropis oculata

Abstract: The effects of trace elements on the lipid productivity and fatty acid composition ofNannochloropis oculata (N. oculata)were studied. The results showed that trace elements had a strong influence on not only the lipid productivity but also the fatty acid composition. The addition of Fe3+, Zn2+, Mn2+, Mo6+, and EDTA and the deletion of Cu2+and Co2+can increase the lipid productivity. The optimum concentrations of the trace elements in the culture medium are 6 times of Fe3+and EDTA, the same concentration of Zn2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 4 publications
2
20
0
Order By: Relevance
“…In addition, trace elements such as molybdenum and cobalt are the important nutritional variables for obtaining high SFAs and total lipid. Dou et al 27 also found that the addition of Fe 3+ , Zn 2+ , Mn 2+ , Mo 6+ , and EDTA can increase the lipid productivity. S. obliquus cultivated in Trenkenshu medium can be used for biofuel because quite high content of palmitic acid obtained in this medium is desirable for good quality biodiesel 12 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, trace elements such as molybdenum and cobalt are the important nutritional variables for obtaining high SFAs and total lipid. Dou et al 27 also found that the addition of Fe 3+ , Zn 2+ , Mn 2+ , Mo 6+ , and EDTA can increase the lipid productivity. S. obliquus cultivated in Trenkenshu medium can be used for biofuel because quite high content of palmitic acid obtained in this medium is desirable for good quality biodiesel 12 .…”
Section: Discussionmentioning
confidence: 97%
“…In nature, the cytoplasmic oil droplets are accumulated under stressful environmental conditions, such as high temperature, light intensity and rise in salinity [19][20][21][22] . In culture, nutritional composition of the medium has more effects on the total lipid content and fatty acid profile, among which nitrogen, silicon and phosphorus have greater roles [20][21][22][23][24] , followed by iron [25][26][27][28] . In 1987, the lipid content and fatty acid composition of Scenedesmus obliquus was determined 29 , but at a later time, the values differed within the species [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some conditions of cultivation should be strategically changed to enhance microalgal lipid. Most recent studies have found that the lipid accumulation in microalgae could be increased through altering parameters such as temperature, light, CO 2 , salinity, and nutrient concentration [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A few reports were available on the effect of ethylenediaminetetraacetate (EDTA) on growth and lipid productivity in microalgae. In Nannochloropsis oculata the dry weight of the biomass and lipid gradually increased with increased concentration of EDTA [10]. The marine diatom Amphiprora paludosa synthesized 65.64% lipid under 0.026 mM of Fe-EDTA [13].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon may be due to the inhibitory effect caused by the high concentration of EDTA present and the combination of EDTA with other trace elements in the Basal medium. Dou et al[29] found the lipid production can be influenced significantly by trace elements of Cu 2+ , Fe 3+ , Zn 2+ , Mn 2+ , Mo 6+ , as well as EDTA and their relative concentrations in microalgae cultures. The effect of temperatures on cell growth of heterotrophic C. protothecoides is shown in…”
mentioning
confidence: 99%